Efforts to Improve Learning Outcomes on Craftsmanship and Entrepreneurship in Vocational School of Project Based Learning (PjBL) Learning Model - Sukrah, Mohammad (Universitas Negeri Padang, 2019)
Based on field data, patterned group learning has not been put into practice in SMK Negeri 6 Malang in a planned manner. The effect of group formation is not visible on learning outcomes, meaning that learning outcomes and learning interests of students are low. Cooperative learning model emphasizes the activities of students in small groups, they work together to help each other in understanding the material business opportunities in the subjects of craftsmanship and entrepreneurship they learn. This learning consciously and deliberately has created an attitude of mutual love to avoid offenses and misunderstandings that can cause animosity among students. This research is a Classroom Action Research using the Project Based Learning (PjBL) learning model as an effort to improve learning outcomes in craftsmanship and entrepreneurship at SMK Negeri 6 Malang specifically the subject matter of handicraft business opportunities. The research findings state that it is proven by the acquisition of the percentage of student learning outcomes criteria, namely in the first cycle there was an increase in learning outcomes by 15 (44.12%) students had reached the KKM, and those who had not yet reached the KKM were known to be 19 (55.88%) participants students. While in cycle II as many as 30 students (88.24%) have been completed while the rest (11.76%) are still below the KKM in the sense of 34 students over 75% above the KKM with an average grade increased from 63 in the first cycle to 84 in cycle II.